FACTORS AFFECTING ENTREPRENEURIAL INTENTION: AN EMPIRICAL STUDY OF STUDENT IN ACEH AND NORTH SUMATERA - Jullimursyida; Mawardati; Mursyidah; Nurul Azmi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research examined the effect of Need for Autonomy, Propensity to Take Risk, Attitude towards Entrepreneurial on Entrepreneurial Intention among students in Aceh and North Sumatera. The data were collected from undergraduate’s students in Aceh and North Sumatera randomly, 120 questionnaires were distributed and 114 responses were collected and analyzed. The findings confirmed the positive relationship between variables of the study, except Attitude towards Entrepreneurial. Need for Autonomy, Propensity to take Risk, Attitude towards entrepreneurial factor account for 43.1% of the variance in Entrepreneurship intention. The study try to give some recommendation for the Universities to be mindful of entrepreneurship to motivate student accumulate intentions to start a business.